2017
DOI: 10.1200/jco.2017.35.4_suppl.310
|View full text |Cite
|
Sign up to set email alerts
|

Interim analysis of a phase 2 study of lenvatinib (LEN) monotherapy as second-line treatment in unresectable biliary tract cancer (BTC).

Abstract: 310 Background: LEN inhibits the activity of vascular endothelial growth factor receptor, fibroblast growth factor receptor, and platelet-derived growth factor receptor–α. These targets have been shown to be expressed in patients (pts) with BTC. The objective of this study is to evaluate LEN as a potential treatment option for these pts. Methods: This is an open-label, phase 2 study conducted in Japan. Pts aged ≥ 20 years with confirmed diagnosis of unresectable BTC, measureable disease per Response Evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Despite small samples and various adverse events, these studies suggest that anti-vascular drugs might be promising for patients with advanced BTC. In addition, the anti-vascular targeting drugs ramucirumab (LY3009806) and lenvatinib, among others, are being investigated in phase II trials for use in treating previously treated advanced BTC (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…Despite small samples and various adverse events, these studies suggest that anti-vascular drugs might be promising for patients with advanced BTC. In addition, the anti-vascular targeting drugs ramucirumab (LY3009806) and lenvatinib, among others, are being investigated in phase II trials for use in treating previously treated advanced BTC (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…No specific trial is looking into the role of GLS1 inhibitors in BTC at this time. However, studies have found that GLS1 is overexpressed in iCCA, and that downregulation of GLS1 expression may suppress cell invasion and migration [ 100 ], making glutamine-directed agents potential future therapies for BTC.…”
Section: Future Directionsmentioning
confidence: 99%